2022
DOI: 10.15586/aei.v50i6.495
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab and allergen immunotherapy for respiratory allergies

Abstract: Although currently approved to treat severe asthma and chronic spontaneous urticaria, omalizumab has also been an effective and safe add-on treatment for other allergic diseases. Namely, omalizumab has been proposed to be used as add-on therapy in patients with allergic rhinitis and asthma and undergoing specific allergen immunotherapy (AIT). AIT is the only treatment that modifies the natural history of IgE-mediated diseases. This brief review summarizes the available evidence and controversies on the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[54][55][56] Omalizumab was also proposed as add-on treatment in patients with allergic rhinitis and asthma undergoing specific AIT. 57 The role of omalizumab as an add-on to OIT or as a monotherapy in children with FA was evaluated by several studies. 58 Regarding PA, Brandström those treated with normal dose (p < .01), as well as higher median ratios for Ara h 2 IgE-ab/IgE (17% vs. 11%).…”
Section: Omalizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…[54][55][56] Omalizumab was also proposed as add-on treatment in patients with allergic rhinitis and asthma undergoing specific AIT. 57 The role of omalizumab as an add-on to OIT or as a monotherapy in children with FA was evaluated by several studies. 58 Regarding PA, Brandström those treated with normal dose (p < .01), as well as higher median ratios for Ara h 2 IgE-ab/IgE (17% vs. 11%).…”
Section: Omalizumabmentioning
confidence: 99%
“…Several studies demonstrated the safety and efficacy of omalizumab in allergic diseases 54–56 . Omalizumab was also proposed as add‐on treatment in patients with allergic rhinitis and asthma undergoing specific AIT 57 . The role of omalizumab as an add‐on to OIT or as a monotherapy in children with FA was evaluated by several studies 58 .…”
Section: Omalizumabmentioning
confidence: 99%
“…IgE antibody production is the most typical immunological response indicative of a food allergy [ 223 , 224 ]. Since an adverse immunological reaction to egg proteins causes atopic dermatitis and eosinophilic esophagitis, it follows that egg allergy is an IgE antibody-mediated allergy [ 225 , 226 ]. Egg proteins’ ability to provoke an immune response is reflected in their stability in the face of heat and enzymatic digestion [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 ].…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…Since an adverse immunological reaction to egg proteins causes atopic dermatitis and eosinophilic esophagitis, it follows that egg allergy is an IgE antibody-mediated allergy [ 225 , 226 ]. Egg proteins’ ability to provoke an immune response is reflected in their stability in the face of heat and enzymatic digestion [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 ]. While both egg components contain proteins that can trigger an allergic reaction, the allergenic potential of EW proteins is greater than that of EY proteins.…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…Thus, when AIT is contraindicated, omalizumab may allow patients to be treated safely with AIT. On the other hand, allergic reactions occurred in some other patients in whom this combined approach was used [16].…”
Section: Anti-ige As An Add-on To Ait In Respiratory Allergymentioning
confidence: 99%